Pengaruh Program Keluarga Harapan (PKH) Terhadap Partisipasi Pendidikan di Kecamatan Indrajaya Kabupaten Pidie - Rusydi Rusydi (Faculty of Economics and Business, Universitas Malikussaleh, 2016)
The purpose of this research is to know the influence of Program Keluarga Harapan Aid (PKH) to Education Participation in Indrajaya Sub-district of Pidie Regency. The population in this study were all household heads receiving PKH assistance in Indrajaya sub-district, Aceh Pidie district. Sampling was done randomly by using “stratisfield random sampling” method as much as 10 percent from 409 respondents to get 41 respondents. The results showed PKH grant funds provided to increase education participation in Indrajaya Sub-district PKH Assistance was able to explain or influence the education participation of KSM children in Indrajya Kabupaten Pidie reached 96.8 percent and the rest of 3.2 percent influenced by other variables outside the model this research. The provision of PKH assistance should be well targeted and truly aimed at improving children’s education. This is important, as such assistance is only temporary and more focused on deciding the poverty chain.Keywords: Program Keluarga Harapan Aid (PKH), Education Participation